Ultramicropore Engineering by Dehydration to Enable Molecular Sieving of H2 by Calcium Trimesate. (29th June 2020) - Mukherjee, Soumya; Chen, Shoushun; Bezrukov, Andrey A.; Mostrom, Matthew; Terskikh, Victor V.; Franz, Douglas; Wang, Shi‐Qiang; Kumar, Amrit; Chen, Mansheng; Space, Brian; Huang, Yining; Zaworotko, Michael J.
Abstract: The high energy footprint of commodity gas purification and increasing demand for gases require new approaches to gas separation. Kinetic separation of gas mixtures through molecular sieving can enable separation by molecular size or shape exclusion. Physisorbents must exhibit the right pore diameter to enable separation, but the 0.3–0.4 nm range relevant to small gas molecules is hard to control. Herein, dehydration of the ultramicroporous metal–organic framework Ca‐trimesate, Ca(HBTC)⋅H2 O (H3 BTC=trimesic acid), bnn‐1‐Ca‐H2 O, affords a narrow pore variant, Ca(HBTC), bnn‐1‐Ca. Whereas bnn‐1‐Ca‐H2 O (pore diameter 0.34 nm) exhibits ultra‐high CO2 /N2, CO2 /CH4, and C2 H2 /C2 H4 binary selectivity, bnn‐1‐Ca (pore diameter 0.31 nm) offers ideal selectivity for H2 /CO2 and H2 /N2 under cryogenic conditions. Ca‐trimesate, the first physisorbent to exhibit H2 sieving under cryogenic conditions, could be a prototype for a general approach to exert precise control over pore diameter in physisorbents. Abstract : Ultramicropore control of molecular sieving in two forms of calcium trimesate leads to the first non‐membrane solid that serves as a molecular sieve for H2 over slightly larger gas molecules, including CO2 and N2 .